Fenugreek (Trigonella foenum-graceum) increases postmenopausal fibroblast-associated COL1A1 and COL3A1 production dominantly through its binding to estrogen receptor beta - Shannaz Nadia Yusharyahya, Kusmarinah Bramono, Andon Hestiantoro, Sarah Qanita Edwar, Indra Kusuma (Journal of Applied Pharmaceutical Science, 2020)
In postmenopausal women, oral or topical administration of estradiol increases skin thickness and collagen synthesis, such as collagen type 1 alpha 1 (COL1A1) and collagen type 3 alpha 1 (COL3A1). Due to undesirable side effects of estradiol, such as risks of breast and endometrium pathology, topical phytoestrogens are alternative treatments for aging-related skin changes. Phytoestrogen is a nonsteroidal substance derived from plants, like fenugreek (Trigonella foenum-graceum L.), which has an estrogen like composition that appears to mimic estradiol. The mechanism of action remains unknown, especially in fibroblast-associated COL1A1 and COL3A1 production. In vitro experiments were conducted using postmenopausal women's fibroblasts with estrogen receptor (ER) antagonists. Cell isolation used explant and enzymatic techniques with ELISA kit (MyBioSource, California) for COL1A1 and COL3A1. Paired student t-tests compared results between control (no treatment), fenugreek extract 2 μg/ml alone, fenugreek extract 2 μg/ml with receptor antagonists for ERα, ERβ, and both receptors. Greater suppresion of COL1A1 and COL3A1 were shown by both antagonists ERα / ERβ group and antagonist ERβ group compared to antagonist ERα group. These results indicate that the fenugreek increases secretion of COL1A1 and COL3A1 through ERα, ERβ, and is mainly mediated by ERβ in post menopausal women’s fibroblasts.
Keywords: COL1A1, COL3A1, estrogen receptors, fenugreek, human dermal fibroblasts.